COLLABORATIVE GOVERNANCE IN DEALING WITH STREET CHILDREN'S PROBLEMS WITH PENTA HELIX APPROACH - Chandra, Pivit Septiary; ilosa, abdiana (Jurnal EL-RIYASAH, 2024)
Children become the shapers of a country. The older generation will put their hopes and ideals in future generations. The quality of future generations is based on the quality of the current child, which is seen from their welfare, which is seen from the development of human resources, starting from the child. The high number of street children indicates that children's welfare needs to be paid more attention. The increase in the number of street children in the last 3 years has the potential to cause social disasters. For this reason, this study aims to look at the role of stakeholders together in collaboration to overcome the problems of street children in the concept of collaborative governance with a pentahelix approach. This study uses a qualitative research method with descriptive analysis. The data acquisition process was obtained from observation, interviews, and documentation. The result of this study is that the government, the private sector, NGOs, academics and the mass media are central objects in the sustainability of handling street children who are always stakeholders. However, the five stakeholders did not move dynamically to realize sustainable collaborative activities.